Do aggressive pro forma earnings-reporting firms have difficulty disclosing intellectual capital? Australian evidence. Issue 5 (26th June 2018) - Yang, Yiru
Abstract : Purpose: The purpose of this paper is to investigate whether aggressive pro forma earnings-reporting firms are difficult in relation to signalling sufficient intellectual capital (IC), and how the market reacts to aggressive pro forma earnings reporting. Design/methodology/approach: Content analysis of 610 annual reports of Australian firms listed on the Australian Securities Exchange 200 is used to obtain IC information. Fixed-effects logistic and ordinary least squares (OLS) regressions are used to examine the hypotheses. Findings: The study finds that aggressive pro forma earnings reporting is negatively and significantly associated with sufficient IC disclosure. Moreover, this paper finds that investors react favourably to aggressive pro forma earnings reporting, and believe that pro forma earnings have greater incremental value-relevance information than statutory earnings. Research limitations/implications: The coding framework used in this study comprises 33 IC items. Other studies have used coding frameworks comprising fewer or more varied IC items. Therefore, when comparing the results of this and other studies, the interpretation of the findings must recognise the differences in approach. Practical implications: Sufficient IC disclosure may help investors to distinguish high-reporting-quality firms and low-reporting-quality firms. The paper demonstrates that aggressive pro forma earnings-reporting firms, which are low-reporting-quality firms, are less likely to disclose sufficient IC. Originality/value: This paper is the first to examine the relationship between aggressive pro forma reporting and IC disclosure. Moreover, this paper built a theoretical framework based on signalling theory to develop research hypotheses, which extend the research on IC underpinned by signalling theory.